“El verbo «ser» en las oraciones seudohendidas y con verbo ser focalizador” - Sedano, Mercedes (El Colegio de México, 2010)
In this paper I examine the grammatical constraints of the verb ser in twotypes of focus constructions in Spanish: pseudo-cleft (“Lo que Juan necesitaes un descanso”, lit. trans. “That which Juan needs is a rest”) and constructionswith ser as the focus verb (“Juan necesita es un descanso”, lit. trans“Juan needs is a rest”). The purpose is to prove that ser does not function asan authentic verb but as a particle which configures the structure in theseconstructions. The data consists of Caracas Spanish recordings, collectedbetween 1977 and 2007. The features of the verb ser which were taken intoaccount for this analysis were: a) verb inflection; b) tense and mood; c) personand number; d) periphrastic forms; e) negatives.